PENGEMBANGAN MODEL PERMAINAN PASS AND GO BASKETBALL DENGAN DOUBLE HOLES TARGET DALAM PENJASORKES PADA SISWA KELAS V SD NEGERI SIWALAN KECAMATAN GAYAMSARI KOTA SEMARANG TAHUN AJARAN 2013/2014 (Department of Physical Education, Sport, Health and Recreation, 2014)
The purpose of this study to generate Development Model Pass And Go Basketball Game with Double HolesTarget Penjasorkes Elementary School Fifth Grade students Siwalan Gayamsari District Semarang AcademicYear 2013/2014